Proposed Marketing Strategy for Nordease - Pradhana, Ferialdi Rasoni; Saphiranti, Dona (The Indonesian Journal of Business Administration, 2013)
The research was conducted to form a strategy in effort to help Nordease overcome the problem. Nordease, as one of the new players in the industry, sees there are a lot of other existing and newly emerged brands that can be definitely regarded as its either main or potential competitor leading to the tight competition. In order to survive in the coming days, the strategy for Nordease was generated through the use of 5C Situation Analysis, which examines both External and Internal Environment covering Company, Collaborators, Customer, Competitor, and Climate. Having finished analyzing the situation , the root cause was found out to be the lack of marketing activities, particularly promotional. Therefore, the proposed strategy is more likely a newly-formed Marketing Mix (Product, Promotion, Price, Place) supported by TOWS Matrix yet the emphasis is focused more on Promotional which will be realized through several programs.Â Keywords: Makerting, Product, Promotion, Place, Price